2018
DOI: 10.1007/s00705-018-3946-z
|View full text |Cite
|
Sign up to set email alerts
|

Mumps epidemiology in Cuba between 2004 and 2015

Abstract: Vaccination with the measles, mumps and rubella vaccine decreased the mumps incidence in Cuba, but in 2006 and 2007 an outbreak with more than 1000 laboratory confirmed cases occurred, mainly among high school and university students. The objective of the study was to investigate mumps epidemiology in Cuba between 2004 and 2015 and provide an in-depth laboratory characterization of selected samples from mumps patients. Samples from 116 cases (throat swabs, urines, paired acute and convalescent serum samples) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…There have been a number of reports of universities being the focal point for outbreaks of mumps around the world [ 2 , 4 , 5 ]. A study evaluating outbreaks between 2010 and 2015 in the United States found that 78% of all of the outbreaks were at universities [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of reports of universities being the focal point for outbreaks of mumps around the world [ 2 , 4 , 5 ]. A study evaluating outbreaks between 2010 and 2015 in the United States found that 78% of all of the outbreaks were at universities [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, even with an effective immunization program in a child population, birth and the vaccination period can generate susceptible after a few years; therefore, vaccination coverage may not be equivalent to population immunity [8]. During the past few decades, the triple viral vaccine has been introduced into immunization policy in several countries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, vaccination coverage may not be equivalent to population immunity. 10 , 11 The triple viral vaccine (MMR) is prepared from live attenuated measles virus (Schwarz, Moraten and Edmonston Zagreb strains), mumps (Jeryl Lynn, L-3 Zagreb and Urabe AM9 strains) and rubella (Wistar strain RA27/3). A study conducted in Finland showed that antibody levels induced by the MMR vaccine decrease progressively after the second dose.…”
Section: Introductionmentioning
confidence: 99%